DAMPAK ISOLASI SOSIAL SELAMA PANDEMI COVID 19 TERHADAP REMAJA : AKTIFITAS, EMOSIONAL, STRESS-ADAPTASI DAN STRATEGI KOPING REMAJA SELAMA PANDEMI COVID-19 DI INDONESIA - Nasrudin, Nasrudin; Kusumaningrum, Umi Azizah; Prihaninuk, Devin (Universitas Pesantren Tinggi Darul Ulum, 2020)
Abstract Adolescence is a period of physical, emotional and social growth that is important for individual development. The Covid 19 pandemic and the policies implemented have an impact on physical, social, emotional life due to limited activities and other restrictions. Adolescents are required to be able to adapt and have positive coping strategies, in order to maintain healthy physical and social emotional conditions during the pandemic. The purpose of this study is to determine the activities, emotional, stress and coping strategies of youth during the covid 19 pandemic in Indonesia. The research design used was descriptive analytic with cross sectional approach with accidental sampling technique. The sample in this study was 92 adolescent respondents, where the research was conducted in East Java, Central Java, Lampung, West Nusa Tenggara and Maluku from 10 to 12 July 2020. The questionnaire used was about the emotional experiences of adolescents related to Covid-19, which consists of 30 question items. The results showed adolescents experienced mild stress due to future uncertainty due to covid-19 amounting to 36 (39.1%), moderate stress due to changes in daily activities during the Covid-19 pandemic was 30 (32.6%), very light stress due to There were 77 (83.7%) of family members infected with covid-19 (83.7%) and coping strategies were used by living with the family of 42 teenagers (45.7%) and exercising and eating a lot to improve the physical condition of 44 teenagers (47, 8%.). The conclusion is that coping strategies by praying, strengthening family functions can help adolescents adapt to face social and emotional problems during the covid-19 pandemic. Keywords: Remaja, Emosional, Stress, Coping, Covid-19